Effect of Continuous Feeding of Ayu-Narezushi on Lipid Metabolism in a Mouse Model of Metabolic Syndrome - Takeshi Nishida; Koichi Tsuneyama; Yasuhiko Tago; Koji Nomura; Makoto Fujimoto; Takahiko Nakajima; Akira Noguchi; Takashi Minamisaka; Hideki Hatta; Johji Imura (The Scientific World Journal)
Ayu-narezushi, a traditional Japanese fermented food, comprises abundant levels of lactic acid bacteria (LAB) and free amino acids. This study aimed to examine the potential beneficial effects of ayu-narezushi and investigated whether ayu-narezushi led to improvements in the Tsumura Suzuki obese diabetes (TSOD) mice model of spontaneous metabolic syndrome because useful LAB are known as probiotics that regulate intestinal function. In the present study, the increased body weight of the TSOD mice was attenuated in those fed the ayu-narezushi-comprised chow (ayu-narezushi group) compared with those fed the normal rodent chow (control group). Serum triglyceride and cholesterol levels were significantly lower in the Ayu-narezushi group than in the control group at 24 weeks of age. Furthermore, hepatic mRNA levels of carnitine-palmitoyl transferase 1 and acyl-CoA oxidase, which related to fatty acid oxidation, were significantly increased in the ayu-narezushi group than in the control group at 24 weeks of age. In conclusion, these results suggested that continuous feeding with ayu-narezushi improved obesity and dyslipidemia in the TSOD mice and that the activation of fatty acid oxidation in the liver might contribute to these improvements.